Temperature effects on polygraph detection of concealed information. (5th October 2015) - MacNeill, A. Luke; Bradley, M. T.
Abstract: Thermoregulatory influences on electrodermal and cardiovascular activity may interfere with the detection of concealed information using a polygraph. This possibility was assessed by means of a mock terrorism scenario. Seventy‐two participants were assigned to either a guilty or an innocent role. They were given a polygraph test at one of three ambient temperatures: 10°C, 22°C, or 34°C. Among guilty participants, electrodermal and cardiovascular measures were least effective at 10°C. Electrodermal results were optimal at 22°C, whereas cardiovascular results were optimal at 34°C. Among innocent participants, the effectiveness of these same measures was not affected by ambient temperature. Temperature had no significant impact on respiration results within the guilty or the innocent groups. Taken together, these findings have implications for those who use polygraphs in uncontrolled testing environments.